Quaility of water for nursery plants irrigation: use of electrical discharges without thermic effect and of electric fields for Meloidogyne incognita Race 1 control - Demattê, João Batista Ioriatti; Tihohod, Dimitry; de Almeida, Alpheu; Demattê, Maria Esmeralda Soares Payão; Perecin, Dilermando (Pesquisa Agropecuaria Brasileira, 1993)
The effect of electrical discharges without thermic effect and of energy field on Meloidogyne incognita Raça 1 larvae elimination in weir water was tested. On an average, 63,22% of larvae were killed by electrical discharges, in comparison with 53,12% of dead larvae in the control (water that received only ammonium sulphate) as an electrolyte. Water exposed to energy fields presented higher percentages of dead larvae (50,01% for electromagnetic field, 43,78% for variable electric field and 40,48% for static electric field) in comparison with control, represented by water without exposition to any energy field and without ammonium sulphate (34,27%).